Respuesta :

Answer: Second option.

Step-by-step explanation:

By the Right Triangle Altitude Theorem, we know that the altitude "h" (Observe the figure attached) is:

[tex]h=\sqrt{9*3}\\h=3\sqrt{3}[/tex]

Then, since we know the value of the altitude, we can calculate the value of "y" with the Pythagorean Theorem:

[tex]a=\sqrt{b^2+c^2}[/tex]

Where "a" is the   hypotenuse and "b" and "c" are the legs of the right triangle.

We can identify that:

[tex]a=y\\b=9\\c=h=3\sqrt{3}[/tex]

Then, substituting values, you get that "y" is:

[tex]y=\sqrt{9^2+(3\sqrt{3})^2}=6\sqrt{3}[/tex]

Ver imagen luisejr77